Effect of Auxiliary Grooves on Molar Crown Preparations Lacking Resistance Form: A Laboratory Study - Po-Ching Lu, BDSc(Hons), GradDipClinDent, DClinDent,1 & Peter Wilson, BDS, FDSRCS, MS, (Journal of Prosthodontics, 2008)
To investigate the effect of auxiliary grooves on resistance to dislodgment of crowns on compromised molar preparations lacking resistance form.